1980
DOI: 10.1038/284017a0
|View full text |Cite
|
Sign up to set email alerts
|

The role of hormone receptors and GTP-regulatory proteins in membrane transduction

Abstract: Cell membrane receptors for hormones and neurotransmitters form oligomeric complexes with GTP-regulatory proteins and inhibit the latter from reacting with GTP. Hormones and neurotransmitters act by releasing the inhibitory constraints imposed by the receptors, thus allowing the GTP-regulatory proteins to interact with and control the activity of enzymes such as adenylate cyclase. This theory may apply generally to membrane signal transduction involving surface receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
489
2
6

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,731 publications
(511 citation statements)
references
References 90 publications
14
489
2
6
Order By: Relevance
“…A number of excellent reviews of this area have appeared [1][2][3]. As a prelude to a discussion of inhibition of adenylate cyclase it seems appropriate to present a brief perspective on stimulation of adenylate cyclase.…”
Section: Stimulation Of Adenylate Cyclasementioning
confidence: 99%
“…A number of excellent reviews of this area have appeared [1][2][3]. As a prelude to a discussion of inhibition of adenylate cyclase it seems appropriate to present a brief perspective on stimulation of adenylate cyclase.…”
Section: Stimulation Of Adenylate Cyclasementioning
confidence: 99%
“…It is clear that higher GTP concentrations are necessary to obtain hormonedependent adenylate cyclase inhibition than hormone-dependent adenylate cyclase stimulation [2]. In [2] it was first proposed that the GTPbinding protein involved in adenylate cyclase inhibition is different from the GTP-binding protein involved in adenylate cyclase stimulation and was called Ni [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that higher GTP concentrations are necessary to obtain hormonedependent adenylate cyclase inhibition than hormone-dependent adenylate cyclase stimulation [2]. In [2] it was first proposed that the GTPbinding protein involved in adenylate cyclase inhibition is different from the GTP-binding protein involved in adenylate cyclase stimulation and was called Ni [2]. Recent studies suggested that Ni is composed of two subunits = a 35 kDa subunit (probably identical to the 35 kDa subunit of Ns) and a 39-41 kDa subunit which can be specifically ADP-ribosylated by the toxin of Bordetella pertussis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The field of signal transduction emerges from the seminal work of Martin Rodbell in the 1970s, where he examined the effects of glucagon on membrane receptors from rat liver cells (1). This led to the 1994 Nobel Prize in Physiology or Medicine that he shared with Alfred Gilman.…”
mentioning
confidence: 99%